Assessment of pain management after orthognathic surgery by the administration of montelukast: An original research - G Jeevan Kumar; Samir Mansuri; Sarin A Nizar; Sameera Qureshi Mohd Rehman; Abhishekh Kumar; Fawaz Abdul Hamid Baig (Journal of Pharmacy and Bioallied Sciences, 2023)
Introduction: Opioid may cause undue risk after surgical procedures like orthognathic surgeries. The present study was aimed to determine how the preoperative administration of oral montelukast affected the degree of postoperative discomfort following bimaxillary orthognathic surgery (BOS). Methodology: This study included all skeletal class III subjects scheduled for BOS. The participants were split into placebo and montelukast groups at random. Every patient received a 10-mL serving of apple juice an hour prior to the surgery; however, for the intervention group, a montelukast 10 mg pill was dissolved in the juice. The same surgical team and general anesthetic guidelines were used for all procedures. The visual analog scale (VAS) was used to calculate postoperative pain at designated intervals. The significance level for the statistical analysis was determined using the Statistical Package for the Social Sciences (SPSS) version 23. Results: The control subjects had a higher level of pain at all the intervals than the intended drug test group. Also, the control group needed more analgesics than the test group. There was one observation made that the length of the surgery had an impact on the postoperative pain. Conclusion: Preoperative montelukast medication may be useful in minimizing postoperative discomfort following bimaxillary orthognathic surgery. More research is required for greater relevance.